Digital Transformation of Mosque-Based Ziswaf Management for Community Economic Independence - Aan Zulyanto; Mardianto Mardianto (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
Mosques hold transformative potential as centers of community economic development in Muslim-majority societies, yet the management of Ziswaf — comprising Zakat, Infaq, Sadaqah, and Waqf — in many mosque institutions remains constrained by manual recording systems, limited transparency, and weak accountability mechanisms. This community service program, conducted in 2025 across two cross-national locations — Songkhla, Southern Thailand, and Kedah, Malaysia — aimed to facilitate the digital transformation of Ziswaf management practices in selected mosque institutions through structured training, system introduction, and ongoing mentoring. A total of 62 mosque administrators, committee members, and community leaders participated across both sites. The program introduced participants to accessible digital tools including spreadsheet-based financial recording systems, WhatsApp-based donor communication channels, and basic social media reporting practices. Post-program assessments demonstrated measurable improvements in administrative efficiency, collection transparency, and community trust in mosque financial management. Several participating mosques successfully transitioned from purely manual to hybrid digital recording systems by the program's conclusion. This article reports on the program methodology, outcomes, implementation challenges, and implications for the sustainability of mosque-based economic empowerment programs in transnational Muslim communities.